PENGARUH PROFITABILITAS, SOLVABILITAS, DAN RASIO PASAR TERHADAP RETURN SAHAM - Rufaida, Ida; Hermanto, Suwardi Bambang (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
This research is meant to examine the influence of profitability, solvability, and market ratio tothe stock return on the companies which are listed in Indonesia Stock Exchange (IDX). The sampleshave been selected by using purposive sampling technique to the 42 property and real estate companieswhich have published their financial statement and their stocks are still actively traded in IndonesiaStock Exchange (IDX) in the 2011-2013 periods, so 126 financial statements which have met thesample criteria have been obtained. The data analysis has been done by using multiple regressionsanalysis with the independent variables i.e.: Return On Asset (ROA), Return On Equity (ROE), Debtto Equity Ratio (DER), Earning Per Share (EPS), Price Earnings Ratio (PER), and the dependentvariable is Stock Return. The result of this research has found that Return On Equity (ROE) andEarning Per Share (EPS) variables have significant influence to the companyâs stock return,meanwhile Return On Asset (ROA), Debt to Equity Ratio (DER) and Price Earnings Ratio (PER)variables do not have any significant influence to the research model.Keywords: Profitability, Solvability, Market Ratio, Stock Return and Multiple Regressions Analysis.